Migrants, Irregular Migrants, or (Irregular) Migrants? - Weatherhead, Katharine T. (Anti-Trafficking Review, 2018)
Response to the ATR Debate Proposition: ‘It is important and necessary to make clear distinctions between (irregular) migrants, refugees and trafficked persons.’ Upon first reading this issue’s debate proposition, I was struck by its structure rather than its content. Its content is subject to lively discussions among scholars, practitioners, and policy-makers, as attested to by other contributions in this issue of the journal. Its curious structure, though, raises issues that merit articulation. In what follows, I briefly problematise the bracketing of the word ‘irregular’ in the debate proposition. What the brackets do is prompt an additional question: migrants, irregular migrants, or (irregular) migrants?